A Multifunctional Ionic Liquid Additive Enabling Stable and Efficient Perovskite Light‐Emitting Diodes. Issue 19 (14th April 2022) - Luo, Yun; Kong, Lingmei; Wang, Lin; Shi, Xingyu; Yuan, Hao; Li, Wenqiang; Wang, Sheng; Zhang, Zhijun; Zhu, Wenqing; Yang, Xuyong
Abstract: The electroluminescence performance and long‐term stability of perovskite light‐emitting diodes (PeLEDs) are greatly affected by the film quality of perovskite emitting layer. Herein, the authors employ an ionic liquid, 1‐butyl‐3‐methylimidazolium trifluoromethanesulfonate ([BMIm]OTf), to manipulate the growth of quasi‐2D perovskite films by providing heterogeneous nucleation sites. The [BMIm]OTf molecules simultaneously realize uniform perovskite films by reducing the contact angles of precursor solution on the hole transport layer (HTL), and eliminate defect states through bonding [BMIm] + cations to negatively‐charged uncoordinated Br and OTf − anions to uncoordinated Pb 2+ defects that effectively suppresses the defect states assisted nonradiative recombination in perovskite films. As a result, the efficiency and the operational lifetime of the resultant PeLED are enhanced by more than twofold and threefold, respectively, achieving a maximum external quantum efficiency of 17.6% and an operational lifetime of over 500 min at an initial brightness of 100 cd m −2 . Abstract : A multifunctional ionic liquid additive is employed to realize uniform, dense and low‐defect perovskite films, based on which the resultant perovskite light‐emitting diodes achieve a maximum external quantum efficiency of 17.6% and an operational lifetime of over 500 min at an initial brightness of 100 cd m −2 .